Fractures of vertebrae and peripheral bones in patients with rheumatoid arthritis (based on long-term observation) - Polina S. Kovalenko; Irina S. Dydykina; Polina O. Postnikova; Svetlana I. Glukhova; Alexander V. Smirnov (Consilium Medicum)
Introduction. In rheumatoid arthritis (RA), fractures occur on average 2–3 times more often than in the general population. Data on the incidence of vertebral fractures in RA is controversial and depends on the detection method.